The rise of the value-added tax / Kathryn James, Monash University, Faculty of Law. - James, Kathryn (College teacher) (Cambridge tax law series., 2015)
This book explores one of the most significant trends in the evolution of global tax systems by asking how, within less than half a century, the value-added tax (VAT) has risen from relative obscurity to become one of the world's most dominant revenue instruments. Despite its significance, very little is known about why so many countries have adopted the VAT and, in particular, why different countries adopt the types of VAT that they do. The popular mythology provides that the merits of the VAT have underpinned its global spread; however, this book contends that much scholarship confuses the question of why the VAT has risen to dominance with the issue of what makes a good VAT. This book combines policy and legal analysis to propose a new way of understanding the rise of this important revenue instrument so as to better reflect the realities of the VATs that are actually implemented.